PENERAPAN PENDEKATAN PEMBERDAYAAN DALAM KEGIATAN PEMBANGUNAN PERTANIAN: Perbandingan Kegiatan P4K, PIDRA, P4MI, dan Primatani (Forum Penelitian Agro Ekonomi, 2020)
Ministry of Agriculture has been long time applied various concept and approach in numerous rural and agricultural development programs. Most of these various concepts were related with popular development paradigm dynamics at world level, such as poverty approach, food security, regional development, sustainable development, gender, and empowerment.  Review analyses extracted from many documents, like guideline books and activity reports indicated that empowerment approach has been the main paradigm in P4K, PIDRA, P4MI and Primatani projects.  In many cases, the process has been considered more important rather than its objectives, efforts to increase accessibility and community control on economic resources, improvement of skills and knowledge, development of local institutions.
Keywords: empowerment; P4K; PIDRA; P4MI; Primatani; pemberdayaan